OPTIMALISASI MEDIA SOSIAL SEBAGAI SARANA PROMOSI EFEKTIF DI RESTO OCEAN GARDEN STASIUN MALANG - Malik, Deni; Irfa’ Billah; Ismi Iftikad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze social media optimization strategies as an effective promotional tool for Resto Ocean Garden Stasiun Malang. In today's competitive digital era, leveraging social media platforms like Instagram has become crucial for enhancing visibility and attracting customers. The research employs a qualitative approach with a case study design, utilizing interviews, observations, and social media content analysis. The findings reveal that implemented promotional strategies - including regular visual content uploads, collaborations with local influencers, and prompt customer responses - have successfully increased engagement, customer visits, and loyalty. However, the study also identifies several limitations, such as the lack of quantitative analysis regarding the effectiveness of each content type and its financial impact. These findings provide practical contributions for culinary business operators in optimizing digital marketing strategies more strategically and measurably.